Large mutual fund families: Bigger may not always be better - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
Investments are vital to one’s financial freedom. But investment strategy is an art which not everybody can master. Those who are new to investing may see mutual funds as an easy tool to make money. It has been traditionally thought that larger mutual fund families tend to perform better than their smaller counterparts. Do they really?